PENDIDIKAN DALAM PERSPEKTIF STRUKTURAL FUNGSIONAL - Binti Maunah (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2016)
This article describes education position in the perspective of functional-structure.  The researcher evaluated and compared various literatures including empirical sources from reseaches as document for review.  Primary data were obtained from recent literatures searching in December 2015.  Data were verified and discussed in a round table discussion and peer-debriefers, involving Islamic teachers team.  Revisions were made after round tablediscussion aspiring comments and suggestions from the forums. The findings or analysis showed that (1) functional-structure theory focuses on social integration, social stability,  value concencus emphasizing harmony perspective and equalibrium, and (2) Education in the functional-structure perspective is encouraged in line with social harmony, equality, and concencus among society to transform social values.